2004
DOI: 10.1534/genetics.167.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Mn2+ Transporter, Smf1p, Is Regulated by Ubiquitin-Dependent Vacuolar Protein Sorting

Abstract: ABSTRACT. Yeast VPS genes play a role in delivery of membrane transporters to the vacuole for degradation, and we show that the vps mutants accumulate elevated levels of the high-affinity Mn 2ϩ transporter Smf1p. cdc1(Ts) conditional growth is also alleviated by mutations, including doa4 and ubc4, that compromise protein ubiquitination, and these ubiquitination defects are associated with Smf1p accumulation. Epistasis studies show that these suppressors require functional Smf1p to alleviate the cdc1(Ts) growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 51 publications
1
33
0
1
Order By: Relevance
“…Therefore, in did4⌬, vps24⌬, and vps4⌬ mutants, proteolytic activity of Prb1p is likely low due to transcriptional repression by Rim101, and thus the low Prb1 activity will in turn result in deficient CPS processing. The previously reported differences in the sensitivity to Ca 2ϩ , Mn 2ϩ , and calcofluor white among mutants in different ESCRT components may also be attributed to the disparity in Rim101 processing (22,66).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, in did4⌬, vps24⌬, and vps4⌬ mutants, proteolytic activity of Prb1p is likely low due to transcriptional repression by Rim101, and thus the low Prb1 activity will in turn result in deficient CPS processing. The previously reported differences in the sensitivity to Ca 2ϩ , Mn 2ϩ , and calcofluor white among mutants in different ESCRT components may also be attributed to the disparity in Rim101 processing (22,66).…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, an srn2⌬ mutant was capable of Rim101 processing and tolerant of LiCl in our analysis, which was the only exception among mutants defective in ESCRT components (data not shown). Bowers et al also reported that srn2 mutants are tolerant of LiCl (13), but Eguez et al reported that these mutants were sensitive (22). The reason for the discrepancy is currently unclear but may reflect somewhat milder phenotypes of srn2 mutants relative to other mutants in ESCRT components, as observed in a higher restrictive temperature for growth, for example (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…Downregulation of the Smf1 manganese transporter, for example, depends on the Bsd2/Tre1/ Tre2 scaffolding system. Smf1 is ubiquitylated, internalized, and targeted to the vacuole in response to high intracellular levels of manganese (Liu and Culotta 1999;Eguez et al 2004). Bsd2, Tre1, and Tre2 possess Rsp5-binding sequences (PPxY ), and these scaffolding proteins are thought to bring the Rsp5 ubiquitin ligase and Smf1 together to facilitate sorting of Smf1 to the MVB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitination of the newly synthesized amino acid permease Gap1 at the Golgi in response to surplus nitrogen is required for its sorting to the vacuole without passing through the cell surface (Risinger and Kaiser, 2008). Similarly, ubiquitination serves as an early determinant for the delivery of the manganese transporter Smf1p along the biosynthetic route to the MVB and the vacuolar lumen (Eguez et al, 2004). We therefore postulate that the newly synthesized and ubiquitinated PHO1 at the ER or Golgi may be redirected en route to the vacuolar lumen for degradation in response to sufficient Pi availability.…”
Section: Pho2-dependent Turnover Of Pho1 In the Emsmentioning
confidence: 99%